RUIN THROUGH PHOTOGRAPH THE CASE OF KAZARMA: KAIAFAS, ILIA - Kolaiti, Ioanna (Design/Arts/Culture, 2020)
This paper deals with the concept of ruin and abandonment through the accompanying photographic material as through also through the understanding of the reality of the photograph itself. Each ruin has its testimonies, traces, findings, photographic evidence, and more. All these unfold before us its history. The research along with the photographic material, compile the narration of the ruin. The main purpose its recognition in the world. Initially, the research site is located in the wider landscape of Lake Kaiaphas in the Gulf of Kyparissia. The events that contributed to the abandonment are recorded. The ruin of Kazarma on Kaiapha beach, in Ilia, is chosen as the main focus of the research. Then, are analyzed the aspects related with the meaning of the ruin and its value through the borrowing of its traces in the area. The photographic material is proposed as a methodology for understanding the ruins, so we can compose a narrative. Finally, as a result of the above, is presented the progression of the research, revealing facts and findings which… have a story to tell.